Pakigbatu sang mga kubus-Janiuaynon folk resistance against Spanish Colonial Rule (1738-1898). - Gerona, Ma. Victoria Gubatanga
This research project inquires into the various forms of resistance exhibited by the Janiuaynon folk against spanish colonial rule. The period covered is from 1738, when Janiuay was subjugated by the Spaniards until the end of the Spanish colonial regime in 1898. Specifically, this paper identified the forms of resistance demonstrated by the folk against the colonial government, gave the factors or reasons that brought about these resistance as well as the measures taken by the colonial authorities in dealing with such resistance. The data were taken from both primary and secondary sources. Primary sources included oral interviews while secondary sources included Pedro Barranco's (1979) manuscript "Maragtas sang Banwa nga Janiuay"., It was found out that the forms of resistance demonstrated by the Janiuaynon folk included flight, banditry and joining the Pulahan movement. They resorted to flight and banditry due to the following factors: refusal to recognize Spanish dominion, fed up of paying high taxes and experiencing other forms of oppression and exploitation. In the case of Pulahan members, they joined the movement for they were attracted to the abilities of this group's leaders and its objectives like freedom from taxes and restoration of village harmony and communalism. The colonial government was threatened by these actions of the folk that it resorted to several means to end their activities. These means included launching of entradas, passage of orders and brutal treatment of captured members. These means, however, only made the natives more angry and violent.